Nuclear casein kinase 2 (CK‐2) activity in human normal, benign hyperplastic, and cancerous prostate - (:unkn) unknown (My University, 1994)
In previous work, we had observed that chromatin‐associated nonhistone protein phosphorylation, catalyzed by intrinsic protein kinase reaction in chromatin preparations from human benign prostatic hyperplasia (BPH) prostate samples was markedly elevated, compared with the normal prostate chromatin samples [Rayan et al: Cancer Res 45:2277‐2282, 19851]. The properties of this protein kinase reaction were suggestive of the involvement of casein kinase(s). By employing the specific synthetic substrate for casein kinase 2 (CK‐2) for assays in cellular fractions, we have shown that this protein kinase is present in human prostate chromatin. Its activity is increased in BPH chromatin by about 25‐fold, as compared with its activity in the normal prostate chromatin. This suggests that CK‐2 is a possible mediator of the enhanced phosphorylation of chromosomal proteins in BPH chromatin. By comparison, CK‐2 activity in chromatin preparations from prostatic carcinoma samples was markedly less elevated than that of the BPH chromatin. Immunohistochemical analysis of the enzyme in human frozen sections of prostate tissue samples showed that the enzyme immunostaining was diffuse in the cytoplasm, but more intense in the nucleus, especially in the nucleoli. In general, the staining corresponded with the en‐zymic data. However, sections from prostatic carcinoma samples appeared to show differential staining, depending on the Gleason's grade of the sample. The samples with higher Gleason's grade showed less intense immunostain in the nucleus, compared with samples of lower Gleason's grade. Further, regions of sections in samples with higher Gleason's grade did not show any immunostaining. These differences in the characteristics of CK‐2 expression in prostatic carcinoma samples may be potentially significant, but need to be evaluated further for their significance to the pathobiology of prostatic neoplasia. © 1994 Wiley‐Liss, Inc. Copyright © 1994 Wiley‐Liss, Inc., A Wiley Company
Keywords: benign prostatic hyperplasia; carcinoma; immunohistochemistry; protein phosphorylation